Evaluation of Natural Science Subject Teachers as Improving the Quality of Student Learning at Madrasah Tsanawiyah - Madyan, Madyan; Atika, Nurul; Selvia, Dora; Hayati, Syamsimar; Salsabilah, Wanada Siti (Integrated Science Education Journal, 2024)
Purpose of the study: The aim of this research is to evaluate the performance of Natural Sciences teachers at MTs Nurul Huda in Muaro Jambi Regency. Methodology: This research uses a descriptive qualitative approach. The sampling technique is the Purposive sampling technique. The sample in this research was the Natural Sciences teacher at MTs Nurul Huda in Muaro Jambi Regency. Data collection in this research was carried out using document analysis and interview techniques. Document analysis using document assessment sheets. The data analysis technique used is the Miles & Huberman technique. Main Findings: Based on the results of interviews with MTs Nurul Huda Natural Sciences teachers in Muaro Jambi Regency, planning, implementation, and assessment were good. Likewise, attention from foundations and school principals should give full attention to teachers so that they can continue to develop their potential and improve their teaching performance. Novelty/Originality of this study: This research can provide a more comprehensive and contextual view in evaluating teacher performance and efforts to improve the quality of learning at MTs Nurul Huda in Muaro Jambi Regency. This can also support updates in general teacher performance evaluation methods in the educational environment.